2010
DOI: 10.1177/1352458510377223
|View full text |Cite
|
Sign up to set email alerts
|

T1 cortical hypointensities and their association with cognitive disability in multiple sclerosis

Abstract: Although T( 1) hypointense NLs may be present in a relatively high proportion of multiple sclerosis patients, the impact that they have in cognitive impairment is not independent from white matter disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…WMSA lesions themselves are pathologically heterogeneous, and it also may not be appropriate to lump them together in one single volume. However, use of T1 to estimate WMSA volume has been reported in other studies using similar methods to what is described here (Bagnato, et al 2010; Burns, et al 2005; Salat, et al 2008). High correlations between WMSAs measured using T1-weighted imaging and those measured using T2-weighted or FLAIR imaging have been established (Benedict, et al 2004; Rovaris, et al 1999; Simon, et al 2000), and it has been suggested that lesions assessed through T1-weighting may in fact show a closer association with clinical symptoms (Bagnato, et al 2010; Miller, et al 1998; Sailer, et al 2001).…”
Section: Discussionsupporting
confidence: 61%
“…WMSA lesions themselves are pathologically heterogeneous, and it also may not be appropriate to lump them together in one single volume. However, use of T1 to estimate WMSA volume has been reported in other studies using similar methods to what is described here (Bagnato, et al 2010; Burns, et al 2005; Salat, et al 2008). High correlations between WMSAs measured using T1-weighted imaging and those measured using T2-weighted or FLAIR imaging have been established (Benedict, et al 2004; Rovaris, et al 1999; Simon, et al 2000), and it has been suggested that lesions assessed through T1-weighting may in fact show a closer association with clinical symptoms (Bagnato, et al 2010; Miller, et al 1998; Sailer, et al 2001).…”
Section: Discussionsupporting
confidence: 61%
“…This T1‐based WMSA volume estimate has been successfully used as a measure of WM lesion volume [Salat et al, 2012], and showed sensitivity in measuring WM lesions in Alzheimer's disease [Salat et al, 2012], as well as to correlate with estimates based on FLAIR acquisitions and to correlate better with clinical symptoms in MS [Bagnato et al, 2010]. …”
Section: Methodsmentioning
confidence: 99%
“…Charil et al, observed a correlation between CI and lesions at the GM-WM junction of associative, limbic and prefrontal cortices [17]. A recent study found that the impact of neocortical lesions on CI is not independent from white matter disease [18]. Correlations have also been found between specific gray matter volumes in the cerebral cortex and cognitive test results.…”
Section: Introductionmentioning
confidence: 99%